2010
DOI: 10.1086/655134
|View full text |Cite
|
Sign up to set email alerts
|

Designing and Reporting Clinical Trials on Treatments for Cutaneous Leishmaniasis

Abstract: Cutaneous leishmaniasis is considered to be one of the most neglected and serious parasitic infectious skin diseases in many developing countries. We have assessed the design and reporting of randomized, controlled trials evaluating treatments included in 2 Cochrane systematic reviews on cutaneous leishmaniasis. The analysis of the methodological quality identified some potential bias that can make it difficult to determine whether truly effective therapies exist for this disease. We found important weaknesses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 78 publications
0
35
0
3
Order By: Relevance
“…This was slightly better in prospective studies, even though typing was done in only 49% of these reports. Based on extensive reviews in the Old World and the New World, Gonzalez et al (19) found similar numbers, with about 50% of clinical studies actually determining the causative species.…”
Section: General Overview Of Pubmed Recordsmentioning
confidence: 88%
See 1 more Smart Citation
“…This was slightly better in prospective studies, even though typing was done in only 49% of these reports. Based on extensive reviews in the Old World and the New World, Gonzalez et al (19) found similar numbers, with about 50% of clinical studies actually determining the causative species.…”
Section: General Overview Of Pubmed Recordsmentioning
confidence: 88%
“…The need to determine the infecting Leishmania species depends largely on the specific context. For clinical and epidemiological studies, confirmation of the infecting species is definitely recommended in all cases (19), preferably using a globally applicable technique that has been validated on all species. In these studies, such an approach is certainly feasible.…”
mentioning
confidence: 99%
“…Treatment may be topical or systemic, but the infecting Leishmania species/strain and geographic region impact treatment efficacy. Few clinical trials have been appropriately designed and reported, 3 especially when compared to the large number of possible combinations of treatments versus Leishmania species versus geographic regions. However, it may be said that because symptoms caused by L. major (Old World) and L. mexicana (New World) generally rapidly self-cure over several months, it is difficult to choose a drug with sufficiently low side effects to give a favorable risk-benefit ratio.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, L. tropica (Old World) CL heals more slowly and is generally treated with local or systemic chemotherapy, and New World CL (non-L. mexicana) is treated either to speed healing or prevent dissemination to the oro-nasal mucosa (mucosal leishmaniasis). [2][3][4] Thus, although these treatment strategies are used, each has uncertain cure rates and therapeutic indices. Several species of Leishmania that cause CL are shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…8 Additionally, nonpharmacological interventions such as cryotherapy, localized controlled heat, and photodynamic therapy are also used to treat the cutaneous type. [9][10][11] In spite of various chemical medicaments applied for the treatment of this disease, results have not yet been satisfactory. Thus, seeking for new and safe medication is considered crucial.…”
mentioning
confidence: 99%